Determinant of Islamic Social Reporting in Sharia Commercial Banks - Safira, Della; Hayati, Mardhiyah; Fasa, Muhammad Iqbal (IAIN Kudus, 2025)
The disclosure of Islamic Social Reporting (ISR) in Islamic Commercial Banks in Indonesia remains relatively low and inconsistent, despite the significant growth in assets and capital in the post-pandemic period. This condition reflects a fundamental issue, namely that financial expansion has not been fully accompanied by an enhancement of social accountability based on Sharia and transparency. This study aims to determine and analyze whether capital size, zakat, and firm size influence Islamic Social Reporting (ISR) in Islamic Commercial Banks in Indonesia during the period 2021–2024. This quantitative study uses secondary data sourced from the annual reports of banks registered with the Financial Services Authority (OJK). The analytical method used is panel data regression software eviews 13. The study population consisted of 14 Islamic Commercial Banks. Through purposive sampling, a final sample of 8 banks was obtained with 4 years of observation, resulting in 32 observations. The Fixed Effect Model was used as the estimation model. The results show that capital size has a significant effect on ISR, firm size also has a positive and significant effect on ISR, while zakat has no significant effect on ISR. Simultaneously, all three variables influence ISR, but partially only capital size and firm size are proven significant. This finding indicates that capital capacity and company scale encourage the expansion of Sharia-based social disclosure, while reported zakat payments have not been the main drivers of ISR quality.